2014
DOI: 10.1587/transinf.e97.d.2147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Conversational Agents on Activation of Communication in Thought-Evoking Multi-Party Dialogues

Abstract: SUMMARYThis paper presents an experimental study that analyzes how conversational agents activate human communication in thoughtevoking multi-party dialogues between multi-users and multi-agents. A thought-evoking dialogue is a kind of interaction in which agents act to provoke user thinking, and it has the potential to activate multi-party interactions. This paper focuses on quiz-style multi-party dialogues between two users and two agents as an example of thought-evoking multi-party dialogues. The experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
(28 reference statements)
0
9
1
Order By: Relevance
“…In addition, the empathic expressions also improved the user ratings of the peer agent regarding intimacy, compassion, amiability, and encouragement. Although [Dohsaka et al 2014] did not find effect of chatbot's self-disclosure on emotional connection, [Lee and Choi 2017] found that self-disclosure and reciprocity significantly improved trust and interactional enjoyment. In [Fitzpatrick et al 2017], seven participants reported that the best thing about their experience with the therapist chatbot was the perceived empathy.…”
Section: Emotional Intelligencementioning
confidence: 80%
See 4 more Smart Citations
“…In addition, the empathic expressions also improved the user ratings of the peer agent regarding intimacy, compassion, amiability, and encouragement. Although [Dohsaka et al 2014] did not find effect of chatbot's self-disclosure on emotional connection, [Lee and Choi 2017] found that self-disclosure and reciprocity significantly improved trust and interactional enjoyment. In [Fitzpatrick et al 2017], seven participants reported that the best thing about their experience with the therapist chatbot was the perceived empathy.…”
Section: Emotional Intelligencementioning
confidence: 80%
“…We identified 13 studies that report emotional intelligence. Unlikely the previously discussed categories, most studies on emotional intelligence focused on understanding the effects of chatbots' empathy and emotional self-disclosure [Ayedoun et al 2017;Dohsaka et al 2014;Fitzpatrick et al 2017;Ho et al 2018;Kumar et al 2010;Lee and Choi 2017;Miner et al 2016;Morris 2002;Portela and Granell-Canut 2017;Shum et al 2018]. Only three papers highlighted emotional intelligence as an exploratory outcome [Jenkins et al 2007;Thies et al 2017;Zamora 2017], where needs for emotional intelligence emerged from participants subjective feedback and post-intervention surveys.…”
Section: Emotional Intelligencementioning
confidence: 99%
See 3 more Smart Citations